Sedimentology and coastal dynamics of carbonate pocket beaches: the Ionian Apulia Coast between Torre Colimena and Porto Cesareo (Apulia, Southern Italy) - Milli, Salvatore; Girasoli, Daniele E.; Tentori, Daniel; Tortora, Paolo (Journal of Mediterranean Earth Sciences, 2017)
This study focuses on a section of the Apulia Ionian-Sea coastline, between Torre Colimena and the town of Porto Cesareo, where pocket beaches of different size and shape are found. The larger pocket beaches comprise individual coastal systems which include coastal-plain, dune, beach and shoreface facies. Absence of sediment-delivering rivers, local production of bioclastic debris from a carbonate factory, and low-volume and thickness littoral prisms are the main characteristics of these pocket systems. The coastal sediments are predominantly bioclastics ranging from coarse to fine, medium-fine, and very coarse sands on the foreshore, upper shoreface, and lower-shoreface respectively. The foreshore and upper shoreface sediments vary according to the amount of exposure to the seas from the west to southeast. Similarly the backshore deposits increase in size with coast exposure. Coastline urbanization and tourist activities have developed extensively during the last 40 years, and most of the erosional signatures have clear connections with nearby human disturbance. Dune degradation related to human activities together with aeolian processes, wave action and a low sediment production from carbonate-factory are the mail factors responsible for the strong erosion that have interested the coastline in the last years. Our topographic survey and sedimentological study indicates that most of the beaches have natural attributes conducive to flooding during marine storms. The substrate topography controls the size and shape of the study pocket beaches, the spatial arrangement of the coastal deposits and the hydraulic and sedimentary processes. Nearshore rip circulation occurs in most of these beaches.